Comparison of laparoscopic appendectomy versus open appendectomy in acute appendicitis in obese diabetic patients (BIRDEM Medical Journal, 2020)
Background: Acute appendicitis (AC) is a common surgical problem requiring emergency hospitalization for urgent appendectomy. In case of diabetic patients, the incidence of developing acute appendicitis including its complications like abscess, gangrene and perforation is higher than non-diabetic. Day by day, laparoscopic appendectomy is having an improved outcome in non-diabetic and non-obese patients. The aim of this study was to compare the outcomes of laparoscopic appendectomy versus open appendectomy in acute appendicitis of obese diabetic patients.Methods: A comparative study was carried out in a tertiary care hospital in Dhaka City. Hospitalized obese diabetic patients with a diagnosis of acute appendicitis, who underwent appendectomy, were considered as study population. Obesity was defined as body mass index (BMI) greater than 30 kg/m2 according to World Health Organization and American Obesity Association guidelines. Patients were divided into two groups according to type of appendectomy; 50 patients by laparoscopic appendectomy as group LA and 50 patients by open appendectomy as group OA.Results: Most patients were obese I (30.0-34.9 kg/m2) in group LA and OA (92.0% and 86.0%, respectively, p